Comparative Analysis of Physicochemical Parameters in Raw and Evaporated Milk from Sebha City, Libya - S.Abuaroos, M. Alhmaly, F. Altohami, M. Erhayem, Kh. Ahmida , Mabroukah Aldarmoon; R. Mohamed (Journal of Pure & Applied Sciences, 2018)
The present study was carried out to determine chemical and physical properties and heavy metals in order to evaluate the potential health risks to humans. A total of fourteen randomly milk samples (7 raw, 3 concentrated and 4 whole milk samples) were collected from different outlets in Sebha, Libya in order to study the physicochemical parameters, minerals and heavy metals of milk samples. The chemical composition was determined by protein, fats, moisture, ash, fibre, carbohydrates. The moisture content (82.6%), pH (6.61), acidity (0.27%), density (1.03g/ml), total solids (16.8%), fat (3.22%), protein (3.16%), total sugar (6.15%), sucrose (1.68g/100ml), NaCl (0.54%), urea (10.48%) were reported. The pH values had the following order: whole>concentrated> raw milk samples. The mean concentrations (mg/l) of metals in analyzed milk samples were ranged between K (4.50E-03), Na (7.00E-03), Ca (20.2E-03), Mg (45.0E-03), Cd (5.60E-03), Zn (4.00E-03).